2009
DOI: 10.1159/000227291
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Lutein on Oxidative Stress in the Term Newborn: A Pilot Study

Abstract: Background: Oxidative stress (OS) plays a crucial role in pathological conditions during the early neonatal period. The newborns are susceptible to oxidative damage due to high metabolic rate and low levels of antioxidant enzymes. Lutein has been found to have protective functions in adult humans as antioxidant. Aim: To evaluate the effects of lutein on OS in newborns. We tested the hypothesis that lutein would act both by increasing antioxidant capacity and inhibiting OS. Methods: This was a randomized, doubl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 51 publications
1
48
0
Order By: Relevance
“…Perrone et al demonstrated a beneficial effect of lutein, selectively accumulating in the retina [14]. Gitto et al indicate the positive influence of even a short-term melatonin therapy on reducing oxidative stress in newborns.…”
Section: Discussionmentioning
confidence: 99%
“…Perrone et al demonstrated a beneficial effect of lutein, selectively accumulating in the retina [14]. Gitto et al indicate the positive influence of even a short-term melatonin therapy on reducing oxidative stress in newborns.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma carotenoid concentrations significantly decline in formula-fed infants immediately following birth compared with their breast-fed counterparts. [17][18][19] Recently, several small studies have approached issues of carotenoid bioavailability 20,21 and putative anti-oxidant effects 16 in preterm newborns. We report the first comprehensive, randomized controlled trial designed to assess feasibility and potential benefits of supplementing preterm infant formulas with the carotenoids lutein, lycopene and b-carotene.…”
Section: Introductionmentioning
confidence: 99%
“…The usefulness of BAP as a clinical marker has been reported in various fields such as neurotrauma and neonatology [8,9]. Measurement of BAP is simple and depends on the chromatic reaction from FeCl 3 - to FeCl 2 -thiocyanate derivatives that reflect serum reducing activity.…”
Section: Introductionmentioning
confidence: 99%